Quantitative Real-Time Polymerase Chain Reaction (PCR) Assay for Rapid Monitoring of the Harmful Algal Bloom Species Cochlodinium polykrikoides - Min-Jeong Kim; Hyun-Jung Kim; Joon Sang Park; Donhyug Kang; Sungho Cho; Hansoo Kim; Seung Ho Baek; Jordan Jun Chul Park; Jeonghoon Han; Kang Eun Kim; Seung Won Jung (Journal of Marine Science and Engineering, 2025)
Harmful blooms of the dinoflagellate Cochlodinium polykrikoides (Margalefidinium polykrikoides) had detrimental aquacultural and economic effects globally, and to reduce the damage caused by these blooms, early biomonitoring and quantitative analysis of C. polykrikoides are of the utmost importance. Here, for the detection of C. polykrikoides using quantitative real-time polymerase chain reactions, we developed specific primers targeting the large subunit ribosomal DNA (LSU rDNA) and evaluated their applicability in the field during the occurrence of a C. polykrikoides bloom. The specific primers not only accurately detected C. polykirkoides but also had a detection performance comparable with that obtained using microscopic observations. Accordingly, we developed a system that can be used in the field and applied when red tides occur, with accurate results being obtained more than five times more rapidly than those obtained based on microscopic analysis. Collectively, our findings indicate that the C. polykrikoides bloom detection system developed in this study can be applied to rapidly detect and accurately quantify C. polykrikoides in environmental samples. Data obtained using this system could be used as a basis for developing prompt monitoring and warning systems for the early detection of C. polykrikoides blooms in the field.